2017
DOI: 10.1177/1753193417727138
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the distal oblique bundle of the interosseous membrane of the forearm: an anatomical study

Abstract: A study was undertaken to examine the presence of the distal oblique bundle of the forearm in a large sample in order to describe its true prevalence. The study sample consisted of 200 cadaveric forearms. Fifteen were excluded due to defects in the distal interosseous membrane. In the remaining 185 specimens, the distal interosseous membrane was examined following removal of soft tissue, to determine whether a distal oblique bundle was present and whether there were connecting fibres to the distal radio-ulnar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
(45 reference statements)
5
20
0
Order By: Relevance
“…In our study, the mean thickness of the bundle was 0.83 mm (range: 0.6 to 1.0 mm). This is comparable to the measurements of Hohenberger et al [4], who report 0.9 mm (range: 0.5 to 1.8 mm) and Dy et al [13], who report 0.85 mm ± 0.28 mm (range: 0.64 to 1.33 mm). Other authors reported thicker DOBs.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, the mean thickness of the bundle was 0.83 mm (range: 0.6 to 1.0 mm). This is comparable to the measurements of Hohenberger et al [4], who report 0.9 mm (range: 0.5 to 1.8 mm) and Dy et al [13], who report 0.85 mm ± 0.28 mm (range: 0.64 to 1.33 mm). Other authors reported thicker DOBs.…”
Section: Discussionsupporting
confidence: 90%
“…In these measurements, we have noticed a high range between the widths of our specimens. The same observation was made by Hohenberger et al [4], who reported a mean width of 9 mm (range: 4 to 19 mm) and also by Noda et al, who reported 4.4 mm ± 1.1 mm (range: 2 to 6 mm) [1].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations